New Product Development : Honey Suction Pump / Fatin Nursuhada Ismail ... [et al.] - Ismail, Fatin Nursuhada; Megat Anuar, Nik Mohamed Azim; Hashim, Nur Ikleil Badriah; Wan Abd Raman, Wan Nurfarihan (2021)
Honey suction pump will support the user with a honey suction system that is inexpensive and simple to use. The overall marketing plan would include the company's unique marketing philosophy and strategy. Our target market will be focused on the residence in Kota Bharu, Kelantan, as our business was nearby and because of this covid19 situations, we need to reduced circle from taking a target for sure that our community member will safe. As a result, for initial intense sales, our organisation has set the target for the kinds of customer segments that our product will provide. Our target client is for honey breeders who work nearby in the Kota Bharu district. Next, our aim is to supply the hardware store to us. At the end of the day, our goal is residence that likes or attracts to buy our stuff. The goods are designed to save time and ease the user, and the price is fair and inexpensive. Plus, we're helping with some imagination to draw people. So, FISA Sdn. Bhd. was introduced to the consumers which are the Honey suction Pump with rechargeable use. It has a new model of our company to be presented to customers, the Honey Suction Pump. Our business is targeting the supply of stingless bee honey, as the honey is now well known and popular among the honey breeders. Honey Suction Pump is an easy-to-use pump that lets users save time and make it easy to suck an infant plus they can charge after use and reuse again for the other suction. As time progresses, the cost of any single item is increasingly rising. There are few baby breeders nowadays who cannot afford a stingless bee system, so it might help them afford it.